2020
DOI: 10.1016/j.expthermflusci.2020.110199
|View full text |Cite
|
Sign up to set email alerts
|

Response of lean premixed swirl tubular flame to acoustic perturbations

Abstract: This study experimentally examined the response of a lean premixed methane/air swirl tubular flame to the longitudinal acoustic perturbations. Experiments were conducted by varying the acoustic frequency (f0), acoustic power (P0) and inlet air flow rate (QA) to systematically study the acoustic-excited flame dynamics, including the flame stability, flame structure, heat release rate and acoustic pressure fluctuations. The results demonstrated that the lean tubular flame was much sensitive to longitudinal pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Bennewitz et al [12] studied the extinction mechanism for a single droplet flame in acoustic standing waves and found that extinction was caused by the temporal increase in the local rate of normal flame strain. This extinction mechanism was also supported by Xiong et al [13][14][15][16]; they further modified the Damköhler number (Da), suitable for acoustic extinction, and the flaming firebrand. Furthermore, droplets can be extinguished when the value of Da drops below 1.0.…”
Section: Introductionmentioning
confidence: 68%
“…Bennewitz et al [12] studied the extinction mechanism for a single droplet flame in acoustic standing waves and found that extinction was caused by the temporal increase in the local rate of normal flame strain. This extinction mechanism was also supported by Xiong et al [13][14][15][16]; they further modified the Damköhler number (Da), suitable for acoustic extinction, and the flaming firebrand. Furthermore, droplets can be extinguished when the value of Da drops below 1.0.…”
Section: Introductionmentioning
confidence: 68%